2015
DOI: 10.1016/j.jvs.2014.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Outcome-based anatomic criteria for defining the hostile aortic neck

Abstract: A limited number of independent anatomic variables are predictive of type Ia endoleak after EVAR, including aortic neck diameter and aortic neck length, whereas mural thrombus in the neck is protective. This study suggests that anatomic measures with identifiable threshold cutpoints should be considered when defining the hostile aortic neck and assessing the risk of complications after EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 25 publications
(31 reference statements)
2
57
2
Order By: Relevance
“…The associations between proximal neck complications and mural neck thrombus and neck calcification are less clear in the literature, which may be caused by the diversity in onset of the complications throughout these studies. 1,2,7,9,14 When comparing our previous study 10 with this one, the results suggest that neck calcification is associated with early complications, while mural neck thrombus is rather associated with late (>1 year) sequelae. Acute complications may be associated with factors that increase the procedure difficulty (tortuous aorta) or immediately impede sufficient fixation and sealing (neck calcification); later failure may be associated with factors that do not provide a stable environment and are prone to change over time (high curvature, mural neck thrombus, and large aneurysm diameter).…”
Section: Discussionmentioning
confidence: 55%
“…The associations between proximal neck complications and mural neck thrombus and neck calcification are less clear in the literature, which may be caused by the diversity in onset of the complications throughout these studies. 1,2,7,9,14 When comparing our previous study 10 with this one, the results suggest that neck calcification is associated with early complications, while mural neck thrombus is rather associated with late (>1 year) sequelae. Acute complications may be associated with factors that increase the procedure difficulty (tortuous aorta) or immediately impede sufficient fixation and sealing (neck calcification); later failure may be associated with factors that do not provide a stable environment and are prone to change over time (high curvature, mural neck thrombus, and large aneurysm diameter).…”
Section: Discussionmentioning
confidence: 55%
“…In spite of the advantages of EVAR as a less invasive technique, in patients with hostile neck anatomy the long-term outcome is still inferior to open surgery [6, 8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, several anatomical factors are taken into account when defining a hostile neck patient: neck length (usually < 15 mm), diameter (> 28 mm) and angulation (> 60°). Other adverse morphological parameters include proximal neck circumferential thrombus or calcification (> 50%) or a tapered/conical neck, wherein the diameter progressively increases between the renal arteries and the sac with a > 2- to 3-mm change over the first 15 mm of the proximal neck [2–6]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,8 Recently, data was published from the ANCHOR registry, a patient cohort with a high prevalence of challenging aortic anatomy and failure of sealing. 9 It was shown that increased infrarenal aortic diameter (>26 mm at the lowest renal artery) and a conical neck configuration were risk factors for type 1A endoleaks.…”
Section: Introductionmentioning
confidence: 99%